Bioaerosol Sensor for In Situ Measurement: Real-Time Measurement of Bioaerosol Particles in a Real Environment and Demonstration of the Effectiveness of Air Purifiers to Reduce Bioaerosol Particle Concentrations at Hot Spots - U Yanagi; Nobuhiko Fukushima; Hideyasu Nagai; Haoyi Ye; Minoru Kano (Atmosphere, 2023)
In this study, we first conducted laboratory experiments on the sensitivity of a newly developed bioaerosol sensor (BAS) suitable for in situ measurements. Then, we performed an in situ test in a shared student space at a university. Furthermore, the effectiveness of ventilation and air purification as a mitigation measure for a location with high concentrations of bioaerosol particles (hot spots) was verified. The experimental results show that the measured values for polystyrene latex are in good agreement with the predicted Mie theory value. They also show a good response to fluorescent particles. The in situ test showed that the BAS fluorescent system does not respond to non-fluorescent particles but only to fluorescent particles. During respiratory infection outbreaks, real-time detection at hot spots and a reduction in particulate matter, including bioaerosols, through ventilation and air purification equipment are effective. In this study, the BAS measurement results showed significant correlations not only with fluorescent particles but also with live bacteria. This does not prove that viruses can be measured in real time. If real-time measurements for viruses become available in the future, the findings of this study will be helpful in mitigating respiratory tract infections caused by viruses.